A Users Guide to Implementing City Competitiveness Interventions : Competitive Cities for Jobs and Growth, Companion Paper 4 - Gashi, Drilon; Watkins, Joanna (World Bank, Washington, DC, 2016)
This paper is framed as a User’s Guide to help city officials and city competitiveness practitioners in implementing interventions. This guide aims to support cities in identifying collaborative configurations of actors from the public and private sector along with the management approaches that can help leadership implement interventions to support the city economy.